2008
DOI: 10.1186/1477-7819-6-120
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma presenting as obstructive jaundice: a case report and review of literature

Abstract: Background: Lung cancer is known to metastasize to the pancreas with several case reports found in the literature, however, most patients are at an advanced stage and receive palliative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Metastatic lung cancer has a very poor prognosis, especially SCLC, and is usually treated with best supportive care or systemic therapy; nonetheless, several reports in the literature suggest that a survival benefit may be achieved by surgical treatment of solitary extracranial spread of non small cell lung cancer [46,47] . This is confirmed by a recent case report regarding a patient presenting with jaundice subsequently diagnosed with a lung adenocarcinoma with a synchronous single metastatic lesion to the pancreatic head [48] . The patient was subjected first to a pancreaticoduodenectomy and then to the removal of the pulmonary lesion; 18 mo after surgery, the patient is asymptomatic and disease-free.…”
Section: Lung Cancersupporting
confidence: 71%
“…Metastatic lung cancer has a very poor prognosis, especially SCLC, and is usually treated with best supportive care or systemic therapy; nonetheless, several reports in the literature suggest that a survival benefit may be achieved by surgical treatment of solitary extracranial spread of non small cell lung cancer [46,47] . This is confirmed by a recent case report regarding a patient presenting with jaundice subsequently diagnosed with a lung adenocarcinoma with a synchronous single metastatic lesion to the pancreatic head [48] . The patient was subjected first to a pancreaticoduodenectomy and then to the removal of the pulmonary lesion; 18 mo after surgery, the patient is asymptomatic and disease-free.…”
Section: Lung Cancersupporting
confidence: 71%
“…In the current study, the two patients presented with weight loss. The most common symptoms of pancreatic metastasis from lung cancer that have been reported in the literature are obstructive jaundice and acute pancreatitis (12,13). Z'Graggen et al (6) reported the first case of GI bleeding following solitary metastasis from lung carcinoma in the head of the pancreas in 1998 (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, when patients with solitary metastasis to the pancreas are carefully evaluated and selected, they become candidates for pancreatic resection, with certain patients achieving long-term survival (6,12,19). As in the present cases, the majority of lung cancer patients suffer from widespread disease that is unresectable (20).…”
Section: Discussionmentioning
confidence: 99%
“…Small cell lung carcinoma with pancreatic metastasis has a bad prognosis. However, when patients with solitary metastases to the pancreas are carefully evaluated and selected, they become candidates for pancreatic resection, with certain patients achieving long-term survival [8,15,16]. As in the present case, the majority of lung cancer patients suffer from widespread disease that is unrespectable [5].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to primary pancreatic carcinoma, the majority of symptoms related to the secondary localizations in the pancreas are not organ-specific, including weight loss, fatigue, abdominal or back pain and jaundice and vomiting [7]. The most frequently reported symptoms of pancreatic localizations from lung cancer are obstructive jaundice and acute pancreatitis [8,9]. Thus, early diagnosis of pancreatic metastasis has an important contribution to perform an immediate and appropriate therapy of the disease especially for solitary lesion.…”
Section: Discussionmentioning
confidence: 99%